A confocal microscopy based method to monitor extracellular pH in fungal biofilms. Issue 5 (19th April 2018) - Schlafer, Sebastian; Kamp, Anja; Garcia, Javier E
Abstract: pH in fungal biofilms is important for a variety of fungal infections and industrial applications involving fungal biofilms, but to date, it has never been measured directly inside the biofilm matrix. In the present study, a new methodology was developed allowing for confocal microscopy based monitoring of extracellular pH inside fungal biofilms. Monospecies biofilms of Aspergillus fumigatus, Candida albicans, Candida dubliniensis and Cryptococcus neoformans were stained with the pH dependent ratiometric probe C-SNARF-4, imaged with a confocal microscope, and a digital image analysis procedure was developed to determine pH in the extracellular matrix. As a proof of concept, pH developments at the biofilm–substratum interface were monitored for 1 h after exposure to glucose. Observed pH drops differed considerably between the different species and also between replicate biofilms of the same species. Candida albicans biofilms showed the highest acidogenicity, with pH drops occurring much faster than in planktonic culture. pH ratiometry with C-SNARF-4 is a valuable tool to get insight into fungal biofilm metabolism and may shed new light on both disease-related and industrially relevant processes in fungal biofilms. Abstract : This work presents a new methodology to measure and visualise pH inside the matrix of fungal biofilms using the pH-dependent dye C-SNARF-4 and confocal laser scanning microscopy.